2013
DOI: 10.3390/ijms140713577
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimetastatic Effect of Phosphatidylinositol 3-Kinase Inhibitor ZSTK474 on Prostate Cancer PC3 Cells

Abstract: Tumor metastasis is the main cause of lethality of prostate cancer, because conventional therapies like surgery and hormone treatment rarely work at this stage. Tumor cell migration, invasion and adhesion are necessary processes for metastasis. By providing nutrition and an escape route from the primary site, angiogenesis is also required for tumor metastasis. Phosphatidylinositol 3-kinases (PI3Ks) are well known to play important roles in tumorigenesis as well as metastasis. ZSTK474 is a specific PI3K inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…A number of studies have demonstrated that girdin expression is dysregulated in several types of malignant tumor, including prostate, breast and colorectal cancer, as well as glioma and ESCCs (10)(11)(12)(13)(14), indicating that girdin may have a role in tumorigenesis. In the present study, it was identified that the expression of girdin was markedly upregulated in esophageal carcinoma samples compared with that in their matched adjacent tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of studies have demonstrated that girdin expression is dysregulated in several types of malignant tumor, including prostate, breast and colorectal cancer, as well as glioma and ESCCs (10)(11)(12)(13)(14), indicating that girdin may have a role in tumorigenesis. In the present study, it was identified that the expression of girdin was markedly upregulated in esophageal carcinoma samples compared with that in their matched adjacent tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, girdin has been demonstrated to participate in the regulation of cell division and migration through cytoskeletal molecules (9). Recently, accumulating evidence has revealed that girdin is involved in numerous different types of malignant tumors in humans, including prostate cancer, breast cancer, colorectal cancer, glioblastoma, as well as esophageal squamous cell carcinoma (ESCC) (10)(11)(12)(13)(14). However, the role of girdin in the regulation of cell proliferation, migration and invasion in ESCC cells remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, hypoxia-inducible factor 1 α (HIF-1 α ) was reported to be up-regulated downstream of mTORC1, and therefore promotes tumor angiogenesis by transcribing vascular endothelial growth factor (VEGF) 33 . By activating NF- κ B and inducing secretion of matrix metalloproteinase (MMP), Akt also promotes cell invasion 34 . However, phosphorylation of S6K negatively regulates insulin receptor substrate (IRS), leading to a negative feedback loop35, 36, 37.…”
Section: Pi3k Critical Element That Is Involved In Carcinogenesismentioning
confidence: 99%
“…The in vivo anti-angiogenic effect was attributed to its dual inhibition mechanism: inhibition of VEGF secretion in cancer cells and direct inhibition of PI3K in endothelial cells 96 . In addition, ZSTK474 inhibited migration and invasion of prostate cancer cell PC3, and blocked the phosphorylation of Girdin and production of MMPs, suggesting the anti-metastatic activity 34 . Like other novel PI3K inhibitors such as NVP-BEZ235, BKM120 and GDC-0941, ZSTK474 inhibits both mutant PIK3CA and the wild type one 56 .…”
Section: Pi3k Inhibitors Approved or In Clinical Trialsmentioning
confidence: 99%
“…In particular, idelalisib (CAL101) has become the first approved PI3K inhibitor for treatment of patients with relapsed chronic lymphocytic leukemia (17). We previously reported that the pan-PI3K inhibitor ZSTK474 exhibited antimetastatic effects via blocking migration and suppressing matrix metalloproteinase secretion of prostate cancer PC3 cells (18). However, there is little information about the role that each individual PI3K isoform plays in cancer cell migration.…”
mentioning
confidence: 99%